How Does Foreign Direct Investment Promote Economic Growth? Exploring The Effects Of Financial Markets On Linkages - Sebnem Kalemli-Özcan; Areendam Chanda; Laura Alfaro; Selin Sayek (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
The empirical literature finds mixed evidence on the existence of positive productivity externalities in the host country generated by foreign multinational companies. We propose a mechanism that emphasizes the role of local financial markets in enabling foreign direct investment (FDI) to promote growth through backward linkages, shedding light on this empirical ambiguity. In a small open economy, final goods production is carried out by foreign and domestic firms, which compete for skilled labor, unskilled labor, and intermediate products. To operate a firm in the intermediate goods sector, entrepreneurs must develop a new variety of intermediate good, a task that requires upfront capital investments. The more developed the local financial markets, the easier it is for credit constrained entrepreneurs to start their own firms. The increase in the number of varieties of intermediate goods leads to positive spillovers to the final goods sector. As a result financial markets allow the backward linkages between foreign and domestic firms to turn into FDI spillovers. Our calibration exercises indicate that a) holding the extent of foreign presence constant, financially well-developed economies experience growth rates that are almost twice those of economies with poor financial markets, b) increases in the share of FDI or the relative productivity of the foreign firm leads to higher additional growth in financially developed economies compared to those observed in financially under-developed ones, and c) other local conditions such as market structure and human capital are also important for the effect of FDI on economic growth.
Keywords: F23; O40; F43; F36; 330